Relationship of Mother Knowledge about Contraceptive Pills and Compliance the Use of Contraceptive Pills in Medan Tuntungan - Nurdiana Manurung; Rizky Andriani Bakara (Journal of Advances in Medicine and Pharmaceutical Sciences, 2022)
Knowledge is the result of "knowing" and this occurs after people have sensed a certain object. Sensing of objects occurs through the five human senses, namely sight, hearing, smell, taste and touch by themselves. The composition of the contraceptive pill contains synthetic estrogen and progestin preparations so that pregnancy can be prevented by suppressing ovulation where the hormones LH and FSH are suppressed, thickening cervical mucus, and preventing thickening of the endometrium. The prevalence of family planning according to family planning devices from active family planning participants in Indonesia is 66.20%. The dominant contraceptive methods are injections (34%) and birth control pills (17%). This study aims to determine the relationship between knowledge of women of childbearing age about birth control pills with adherence to the use of birth control pills. The research methodology in this study used analytical observation with a cross sectional approach, 40 samples by purposive sampling, in Baru Ladang Bambu, Medan Tuntungan. Based on the results of statistical analysis obtained by 40 respondents, it can be concluded that there is a relationship between the knowledge of women of childbearing age about birth control pills with adherence to the use of birth control pills, which means that the better the knowledge of women of reproductive age couples, the more obedient in the use of birth control pills.